Violence against women:: Study of the cases filed at Caaguazu's Prosecution Office's Victims Assistance Center (Legal journal - Research in Legal and Social Sciences, 2020)
This research reflects the increase of the request for Psychological Assessments, filed at the Caaguazu's Prosecution Office's Victims Assistance Center, whereit could be spotted that most of the people who attend the mentioned center are women, and the agressors, in turn, men; henceforth, there was the need to know theparticular characteristics of the punishible offenses filed at the office. Consequently, the reference point was the statistical record for the period january to december2018. At this juncture, it shows what is considered as “Violence against women”, together with the types of violence, the risk factors, and the psychological harmsthat can be done to the victims; besides, it could be detailed how these offenses occur in Caaguazu and the neighboring cities.
Keywords: women; violence; types; risk factors; psychological harm